Monumentalitas Hibrida dan Perlawanan Ruang dalam Arsitektur Indonesia Pasca-Kolonial - I Putu Udiyana Wasista; Anak Agung Gede Rai Remawa; I Kadek Dwi Noorwatha; I Made Bayu Pramana (LP2M ISBI Bandung, 2026)
This study analyzes tensions between indigenous cosmology and Indonesian nationalism in the Monumen Perjuangan Rakyat Bali as an expression of Hindu Balinese spatial logic responding to modern nation-building. A qualitative interpretive approach employs semi-structured interviews with architects and historians, along with systematic document analysis. Lefebvre’s spatial triad and Bhabha’s hybridity frame the analysis. Findings show the monument as a sedimented temporal space where mythological and historical narratives coexist without final synthesis. Use of the Samudramanthana epic in nationalist pedagogy produces cultural differentiation rather than a unified identity. Popular adoption of the vernacular name Bajra Sandhi reflects a form of semantic reappropriation privileging religious over nationalist identification. Construction across three gubernatorial administrations indicates ongoing hegemonic negotiation. The study concludes that postcolonial monuments operate as agonistic spaces enabling contestation of meaning while advancing understanding of spatial politics where local cosmology intersects with state projects.